Insights on Guerbet Reaction: Production of Biobutanol From Bioethanol Over a Mg–Al Spinel Catalyst - Portillo Crespo, M. A.; Vidal-Barrero, F.; Azancot, Lola; Reina, Tomas Ramírez; Campoy, M. (Frontiers in Chemistry, 2022)
The production of biobutanol from bioethanol by the Guerbet reaction is an alternative pathway to renewable sources. The commercial viability of this green route requires improvements in the process development. This study experimentally examines the influence of operating conditions on the performance of a Mg–Al spinel catalyst prepared from hydrotalcite precursors. This catalyst demonstrates an exceptional performance in the Guerbet reaction with a promising activity/butanol selectivity balance, excellent long-term stability, and very-low-carbon footprint (CO2 generation as by-products is minimal). This study showcases a systematic strategy to optimize the reaction parameters in the Guerbet reaction for biobutanol production using an advanced spinel catalyst. Upon carefully adjusting temperature, pressure, space velocity, and reactants co-feeding, very promising conversion (35%) and butanol selectivity values (48%) were obtained.